KONSEP “LÈBUR ÈABES” PADA PENATAAN TATA LETAK TOKO KELONTONG MADURA: “LÈBUR ÈABES” CONCEPT IN MADURA GROCERY STORE LAYOUT - Ardan Dikri Purnama; Krishna Hutama; Yan Yan Sunarya (Universitas Trisakti, 2026)
“Lèbur Èabes” Concept In Madura Grocery Store Layout. Toko kelontong Madura reflect a a unique blend of local cultural values and adaptive design principles. This study explores how the concept of